2020
DOI: 10.18235/0002901
|View full text |Cite
|
Sign up to set email alerts
|

Nudging Parents to Improve Preschool Attendance in Uruguay

Abstract: Uruguay has increased it preschool enrollment, reaching almost universal coverage among four- and five-year-olds. However, more than a third of children enrolled in preschool programs have insufficient attendance, with absenteeism higher in schools in lower socioeconomic areas and among younger preschool children. This paper presents the results of a behavioral intervention to increase preschool attendance nationwide. Most previous experiments using behavioral sciences have looked at the impact of nudging pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…The magnitude of absences and chronic absenteeism across all schools (Comparison Schools, UBC Schools that did not prioritize attendance, and UBC Schools that prioritized assistance) indicates that this problem is widespread and enduring. These findings are consistent with one study from Uruguay that reported that one third of children enrolled in preschool were absent for more than 15% of school days (Díaz et al, 2020). Data from around the world about daily attendance by preschoolers is scant (most studies have focused on preschool attendance as a binary variable, more reflective of preschool access and uptake; Gong et al, 2015;Boo, 2016;Delprato et al, 2016;Woldehanna, 2016;Sun et al, 2018;Su et al, 2020).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The magnitude of absences and chronic absenteeism across all schools (Comparison Schools, UBC Schools that did not prioritize attendance, and UBC Schools that prioritized assistance) indicates that this problem is widespread and enduring. These findings are consistent with one study from Uruguay that reported that one third of children enrolled in preschool were absent for more than 15% of school days (Díaz et al, 2020). Data from around the world about daily attendance by preschoolers is scant (most studies have focused on preschool attendance as a binary variable, more reflective of preschool access and uptake; Gong et al, 2015;Boo, 2016;Delprato et al, 2016;Woldehanna, 2016;Sun et al, 2018;Su et al, 2020).…”
Section: Discussionsupporting
confidence: 83%
“…Text-based interventions have been shown to reduce chronic absenteeism from 63 to 55.3% of children enrolled in Head Start classrooms in Chicago (Kalil et al, 2021), and from 26 to 13% of children enrolled in kindergarten in Pittsburgh (Smythe-Leistico and Page, 2018). A text-based intervention for parents of children enrolled in prekindergarten and kindergarten in Uruguay increased attendance by 0.32-0.68 days over the 13-week period among children whose baseline attendance was in the 25th, 50th and 75th quantiles (Díaz et al, 2020). A mail-based intervention decreased chronic absenteeism from 5.5 to 4.6% of children in 10 preschools in California (Robinson et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Play varies widely across and within cultures as a result of differences in childrearing beliefs, values, and practices, including the types of social interactions experienced during play, the resources used for playing, and the relation play has to other everyday activities; this necessarily has an impact on the quality and quantity of play (Gaskins, Haight, and Lancy, 2017). Parents with lower resources often miss opportunities to play a role as active agents in their child's development and learning because poverty can drain their cognitive resources and because their decisions may be tied to cognitive biases, such as limited attention and "present bias" (Gennetian, Darling, and Aber, 2016;Mateo-Berganza et al, 2020). That is, income instability and scarce resources may cause parents to discount future losses compared with present needs.…”
Section: Introductionmentioning
confidence: 99%